2020
DOI: 10.31237/osf.io/bv6pj
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Partial Carrier-Phase Integer Ambiguity Resolution for High Accuracy GNSS Positioning

Abstract: Global navigation satellite systems provide ranging based positioning and timing services. The use of the periodic carrier-phase signals is the key to fast and accurate solutions, given that the inherent ambiguities of the carrier-phase measurements are correctly resolved. The idea of partial ambiguity resolution is to resolve a subset of all ambiguities, which enables faster solutions but does not fully exploit the high precision of the carrier-phase measurements. Theory, methods, and algorithms for partial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 97 publications
0
8
0
Order By: Relevance
“…Defining the mapping S(⋅) ∶ ℝ n → ℤ |J| , the index set J can assume any of the 2 n − 1 possible non-empty realizations that follow from either including each of the n elements of the parameter vector a or not. Such an estimator can be fully described by the regions S z ⊂ ℝ n , ∀z ∈ ℤ |J| , which denotes the point set that is mapped to the same integer z via S(⋅) (Brack 2019) Then, by considering the integer constraint of ambiguity, the float solution is fixed as the integer solution, which is achieved through many-to-one mapping. The partial integer estimator corresponding to these regions can be explicitly written as: This is of importance when formulating the constraints that have to be imposed on the construction of the regions S z .…”
Section: Partial Ambiguity Resolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Defining the mapping S(⋅) ∶ ℝ n → ℤ |J| , the index set J can assume any of the 2 n − 1 possible non-empty realizations that follow from either including each of the n elements of the parameter vector a or not. Such an estimator can be fully described by the regions S z ⊂ ℝ n , ∀z ∈ ℤ |J| , which denotes the point set that is mapped to the same integer z via S(⋅) (Brack 2019) Then, by considering the integer constraint of ambiguity, the float solution is fixed as the integer solution, which is achieved through many-to-one mapping. The partial integer estimator corresponding to these regions can be explicitly written as: This is of importance when formulating the constraints that have to be imposed on the construction of the regions S z .…”
Section: Partial Ambiguity Resolutionmentioning
confidence: 99%
“…In other words, the probability of correct ambiguity estimation, i.e., ambiguity success rate P s , is equal to the probability that â resides in the pull-in region P a with a being the true but unknown ambiguity vector (Brack 2019):…”
Section: Integer Ambiguity Verification In the Probability Domainmentioning
confidence: 99%
“…Although data-and model-driven schemes are widely used, they only take into account the ambiguities derived from the real-valued parameters estimation and the information brought by the covariance matrix of the ambiguities. While the requirement of a minimal precision for the fixed solution has been discussed in the context of PAR [18] (Ch. 4), its consideration as subset selection criteria has not yet been proposed.…”
Section: Precision-driven Par Schemementioning
confidence: 99%
“…Answering this question leads to the different selection heuristics, such as signalto-noise ratio [11,12], Ambiguity Dilution of Precision (ADOP) [13], or minimum bias [14]. Alternatively, the framework of Generalized Integer Aperture (GIA), introduced by Brack in his series of work [15][16][17][18], extends the concepts from Integer Aperture to PAR to jointly perform real-to-integer mapping and subset selection.…”
mentioning
confidence: 99%
“…Verhagen and Teunissen [ 13 ] proved that this estimator is always optimal in terms of the MSE, while Wen et al [ 14 ] demonstrated the use of the BIE estimator for GNSS precise point positioning (PPP). In Brack et al [ 15 ] and Brack [ 16 ], a sequential BIE approach was developed. Subsequently, Teunissen [ 17 ] extended the theory of integer equivariant estimation by developing the principle of BIE estimation for the class of elliptically contoured distributions, while Odolinski and Teunissen [ 18 ] analyzed the BIE performance for low-cost, single- and dual-frequency, short- to long-baseline multi-GNSS RTK positioning, and they found that the BIE positions reveal a ‘star-like’ pattern when the ILS SRs are high.…”
Section: Introductionmentioning
confidence: 99%